FRI0460 Extra-articular manifestations in patients with axial spondyloarthritis: a cross sectional study from southern denmark. (15th June 2017) - Andreasen, RA; Christensen, R; Kristensen, LE; Ellingsen, T; Horn, HC; Hansen, IMJ
Abstract : Background: Axial (ax) spondyloarthritis (SpA) is a heterogenous group of chronic rheumatic diseases. Ax-SpA is subdivided into two groups referred to as nonradiographic and radiographic (i.e. AS) respectively. Next to the spinal and articular symptoms, many patients with SpA also have extra-articular manifestations (EAM) which contribute to reduced quality of life 1 . SpA appears to be more frequent in men than woman in its axial presentations, and in reference to the prototype of the disorder, AS, three male cases are documented for every female case. However, since the introduction of the new ASAS criteria for ax-SpA these differences are no longer so apparent 2 . Nevertheless, little is known of the differential clinical expression of SpA between males and females. Objectives: The objective of this study was to compare patients with AS and nr-axSpA stratified by gender, using standardized clinical tools (including patient-reported outcomes (P-ROs)) and C-reactive protein (CRP) level as a biomarker for inflammation. Methods: Ax-SpA patients were included prospectively and underwent an examination program at one visit. We used ASAS criteria and the modified New Yorker criteria for classification. Information on demography and PROs was obtained. A trained physician performed a clinical examination, and BASMI and the The Spondyloarthritis Research Consortium of Canada Enthesitis Index (SPARCC) was used to enthesitis count. Chi-square and t-tests were used for categorical and continuous variables respectively to test the null hypothesis. Results: Eighty patients with ax-SpA were included. Table 1 shows the results (mean ± SD or relative frequency) for the comparison of demographic and disease characteristics between clinical subgroups. Conclusions: For the PROs, BASDAI and pain were higher in females diagnosed with nr-axSpA, and the CRP was significantly lower in this group. Peripheral and EAMs were slightly equally prevalent in AS and nr-axSpA in men and women except for uveitis, which is slightly more prevalent in AS. Our data show that AS patients were more frequently male than nr-axSpA patients. These results are in line with previous studies showing that male patients with axial SpA have more structural damage on radiographs than female patients. Among women, this study indicate that pain is more pronounced in non-radiographic axSpA than in AS, potentially revealing that chronic widespread pain (e.g. fibromyalgia) might interfere with the diagnostic accuracy of the non-radiographic axSpA subgroup. However, despite the absence of radiographic changes, patients with nr-axSpA have a burden of illness, with self-reported disease activity and functional impairments comparable with those of patients with structural changes consistent with AS. References: Braun J, Kiltz U, Baraliakos X, et al. Optimisation of rheumatology assessments - the actual situation in axial spondyloarthritis including ankylosing spondylitis. Clinical and experimental rheumatology 2014;32(5 Suppl 85):S-96–104. Gran JT, Ostensen M, Husby G. A clinical comparison between males and females with ankylosing spondylitis. The Journal of rheumatology 1985;12(1):126–9. Disclosure of Interest: None declared